Heidegger and Social Ecology - Cole, Daniel (Stance: an international undergraduate philosophy journal, 2019)
In this essay I defend Heidegger’s critique of technology against possible criticisms that he may be an anti-humanist and a mystic. This essay will show that Heidegger’s critique of technology is helpful in thinking about ecological questions; and his contributions to such questions is relevant and not radically separated from some of the work of other philosophers today including Karen Warren and Marilyn Frye.